MENELISIK IMPLIKASI HUKUM: ANALISIS KEPEMILIKAN HAK ATAS KEKAYAAN INTELEKTUAL PADA PLATFORM CRYPTOKITTIES - Maulana, Muhammad Asrul; Santosa, Shilla Hasmara (Wacana Hukum, 2023)
This research analyzes the legal implications related to the ownership of intellectual property rights on the CryptoKitties platform. CryptoKitties is a blockchain-based gaming platform that allows users to buy, own, and trade unique virtual cats. These cats are represented by digital assets called non-fungible tokens (NFTs), which grant exclusive ownership to their owners. This research uses a normative method with a statutory approach. Accordingly, the user acknowledges and agree that Dapper (or, as applicable, the licensor) has all legal rights, ownership, and interests in and to all other elements of the application, and all intellectual property rights therein, but the ownership of non-fungible token (NFT) intellectual property is fully owned by the user. And Dapper grants exclusive rights to the user over the digital assets representing unique virtual cats.